The effect ofintensity of speed competitionexercises in the heavy competence speed in the ascending hierarchical method in developing some physical abilities and the achievement of 100 m running competition under the age of 20 - SABEEH KAREEM, WISAL (International Journal of Psychosocial Rehabilitation, 2020)
There are many factors that affect training and achievement development, including the use of methods and training methods, and that the choice of regulated exercises contribute to the development of the level of athletic performance because they have a direct impact on achieving achievement and thus be a clear indication of the development of the athlete and bring him to higher levels, and the goal of the research is to prepare and identify exercises Strongly the speed of competition with weighting in the ascending hierarchical method in developing some physical abilities and accomplishing the 100-meter sprint under 20 years, and the research imposed exercises strongly with the speed of competition by weighting in the ascending hierarchical method in developing some physical abilities and achieving a 100-meter sprint under 20 years old. And she took it The researcher has an experimental approach by designing the two equal experimental and control groups and determining the research community for a competition of 100 meters young men with (12) runners under the age of 20. The speed of competition with weighting exercises was applied in a hierarchical way up on the experimental group for a period of eight weeks and by three training units per week. The researcher used Statistical Portfolio (spss) To process the data and the researcher reached the most important conclusions that can be relied upon in developing physical abilities and accomplishing other competitions (200 meters, 400 meters, 110 meters hurdles, 400 meters hurdles), as their achievement is linked to achieving the shortest possible time.